2023
DOI: 10.3390/pharmaceutics15030777
|View full text |Cite
|
Sign up to set email alerts
|

Future Pharmacotherapy for Sensorineural Hearing Loss by Protection and Regeneration of Auditory Hair Cells

Abstract: Sensorineural hearing loss has been a global burden of diseases for decades. However, according to recent progress in experimental studies on hair cell regeneration and protection, clinical trials of pharmacotherapy for sensorineural hearing loss have rapidly progressed. In this review, we focus on recent clinical trials for hair cell protection and regeneration and outline mechanisms based on associated experimental studies. Outcomes of recent clinical trials provided valuable data regarding the safety and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Numerous signaling pathways and factors, such as Notch, Wnt, and Atoh1, emerge as promising candidates to further investigate in hair cell regeneration studies within clinical trials. Several ongoing clinical studies are exploring the efficacy and safety of these pathways as potential therapeutic targets for hearing loss and in translational research in this field (ISRCTNregistry, 2017;ClinicalTrials.gov, 2022a,b;EU Clinical Trials Register, 2022;Matsunaga and Nakagawa, 2023).…”
Section: Figurementioning
confidence: 99%
“…Numerous signaling pathways and factors, such as Notch, Wnt, and Atoh1, emerge as promising candidates to further investigate in hair cell regeneration studies within clinical trials. Several ongoing clinical studies are exploring the efficacy and safety of these pathways as potential therapeutic targets for hearing loss and in translational research in this field (ISRCTNregistry, 2017;ClinicalTrials.gov, 2022a,b;EU Clinical Trials Register, 2022;Matsunaga and Nakagawa, 2023).…”
Section: Figurementioning
confidence: 99%
“…Although research on human inner ear regeneration has just started, some researchers have initiated clinical trials targeting either cochlear endogenous progenitor cells or ribbon synapses as a treatment for SNHL in adults (for an extended review on this topic, see [192,193]). The REGAIN clinical trial (EudraCT number 2016-004544-10) reported positive results from a phase I multiple ascending dose, open-label safety study of a novel gamma-secretase (Notch) inhibitor (LY3056480) in 15 patients with mild to moderate SNHL.…”
Section: Human Inner Ear Regeneration and Clinical Trials Targeting E...mentioning
confidence: 99%
“…Furthermore, a pioneer clinical trial has already shown that modulating Wnt (CHIR99021) and Notch (LY411575) signaling pathways with a recently commercialized drug (FX322) in patients with SNHL improves speech recognition in-quiet and in-noise 90 days after treatment [194]. Several clinical trials are ongoing to test the efficacy of FX322 to improve hearing in stable, acquired, adult-onset SNHL associated with noise-induced, idiopathic sudden, and age-related SNHL [192]. No results have yet been published on these ongoing clinical trials.…”
Section: Human Inner Ear Regeneration and Clinical Trials Targeting E...mentioning
confidence: 99%
“…Sensorineural hearing loss (SNHL) is a common otolaryngologic disorder characterized by damage to the auditory nerve resulting in decreased or complete loss of hearing ( Gregory et al, 2023 ; Matsunaga and Nakagawa, 2023 ; Zine and Fritzsch, 2023 ). The incidence of this disease has been increasing in recent years, which may be associated with factors such as fast-paced lifestyles, high-intensity work, and environmental noise pollution in modern society ( Al-Azzawi and Stapleton, 2023 ; Saba et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%